PENGARUH METODE OUTDOOR STUDY TERHADAP HASIL BELAJAR SENI RUPA KELAS X DESAIN INTERIOR SMK NEGERI 4 PADANG - Fika Febriani, Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2019)
This research aims to observe the effect of the Outdoor Study method toward the student learning outcomes in the subject of the Basic Creativities through the differences of the student learning outcomes in the experimental class with the control class. The learning material is the types of artistical creativity development at class X of the Interior Design. The researcher has conducted this research at SMK Negeri 4 Padang on November 7-30, 2018. The research instrument is the test of the student learning outcomes. Therefore, the result of the research is the student learning outcomes using the outdoor study method contrasts with the student learning outcomes using the conventional method. The post-test result is 0,000 among the significant level criteria is 0.05.Keywords: Outdoor Study, learning outcomes, significant